New Trends in Energy Harvesting from Earth Long-Wave Infrared Emission - Luciano Mescia; Alessandro Massaro (Advances in Materials Science and Engineering)
A review, even if not exhaustive, on the current technologies able to harvest energy from Earth’s thermal infrared emission is reported. In particular, we discuss the role of the rectenna system on transforming the thermal energy, provided by the Sun and reemitted from the Earth, in electricity. The operating principles, efficiency limits, system design considerations, and possible technological implementations are illustrated. Peculiar features of THz and IR antennas, such as physical properties and antenna parameters, are provided. Moreover, some design guidelines for isolated antenna, rectifying diode, and antenna coupled to rectifying diode are exploited.